Home appliances control device system based on Bluetooth and Global Mobile System / Muhammad Haziq Hashim … [et al.] - Hashim, Muhammad Haziq; Mohd Azmi, Muhammad Hafiq; Hasan, Khairul Kamarudin; Hairuddin, Muhammad Asraf; Abdul Majid, Masmaria (Division of Research and Industry Linkages, 2017)
There are user having problem such as always forgot do the simple thing example switch off the electrical appliances when go work or spent time with family at outside. Then has old people or handicap person need some have for switch off or on the electrical appliances because not easy for them to walk go to near switch. Home Appliances Control Device System Based on Bluetooth and Global Mobile System (GSM) Technologies also provide safety by alerting user when the home device is operation or not. In this project also provide comfortable life for user because user easy monitors electrical appliances in outside and inside. This project has added some different from the other idea example buzzer to alert user will device operation or not operation. The operation of this project is user can send the chosen code for switch on or off fan or lamp at home just thought the GSM and Bluetooth, the condition of all home appliances was display on LCD and user mobile phone. Furthermore, this project achieves the objective to build the home appliances control device system by using Bluetooth and GSM as a medium switching and analyse the effectiveness of the home appliances control device system in order to avoid electricity wastage. Based on all the info can see the potential this project for provide comfortable lifestyle for user and this project.